The Effectiveness of Predict Observe Explain (POE) Model with PhET to Improve Critical Thinking Skills of Senior High School Students - Ilfi Fatimah Alfiyanti; Budi Jatmiko; Wasis (Studies in Learning and Teaching, 2020)
This study is aimed to determine the effectiveness of predict observe explain (POE) model with PhET to improve critical thinking skills of senior high school students. The sample used was the grade eleven students of SMA N 18 Surabaya consist of 60 students. This type of research was pre-experimental with one group pre-test post-test design. Research data is obtained from the result of pre-test and post-test of students' critical thinking skills and responses after learning activity. Data analysis techniques used N-gain and Wilcoxon test. The result of the study shows that the score of students' critical thinking skills in grade eleven of Group 1 and Group 2 increase after the implementation of predict observe explain (POE) learning model with PhET and both of them present positive responses to the learning component and show a good interest. Based on the data analysis result, it can be concluded that predict observe explain (POE) model with PhET is effective to use to improve the critical thinking skills of senior high school students.